A pregnancy hormone-cell death link promotes enhanced lupus-specific immunological effects - Sachdeva, Ruchi; Pal, Rahul (Frontiers in Immunology, 2022)
Women of reproductive age demonstrate an increased incidence of systemic lupus erythematosus, and reproductive hormones have been implicated in disease progression. Additionally, pregnancy can be associated with disease “flares”, the reasons for which remain obscure. While apoptotic bodies are believed to provide an autoantigenic trigger in lupus, whether autoantigenic constituents vary with varying cellular insults, and whether such variations can be immunologically consequential in the context of pregnancy, remains unknown. As assessed by antigenicity and mass spectrometry, apoptotic bodies elicited by different drugs demonstrated the differential presence of lupus-associated autoantigens, and varied in the ability to elicit lupus-associated cytokines from lupus splenocytes and alter the phenotype of lupus B cells. Immunization of tamoxifen-induced apoptotic bodies in lupus-prone mice generated higher humoral autoreactive responses than did immunization with cisplatin-induced apoptotic bodies, and both apoptotic bodies were poorly immunogenic in healthy mice. Incubation of lupus splenocytes (but not healthy splenocytes) with the pregnancy hormone human chorionic gonadotropin (hCG) along with tamoxifen-induced apoptotic bodies (but not cisplatin-induced apoptotic bodies) induced increases in the secretion of lupus-associated cytokines and in the up-modulation of B cell phenotypic markers. In addition, levels of secreted autoantibodies (including of specificities linked to lupus pathogenesis) were enhanced. These events were associated with the heightened phosphorylation of several signaling intermediates. Observations suggest that hCG is a potential disease-promoting co-stimulant in a lupus-milieu; when combined with specific apoptotic bodies, it enhances the intensity of multiple lupus-associated events. These findings deepen mechanistic insight into the hormone’s links with autoreactive responses in lupus-prone mice and humans.